Coal tar refining by aromatic-aliphatic solvent extraction for preparing QI-free pitch. (4th March 2020) - Wang, Yonggang; Hu, Jianhong; Liu, Dan; Liu, Zhe; Zhang, Haiyong; Zhang, Shu
To obtain suitable material for making needle coke, the aromatic and aliphatic solvents were blended for extracting desirable compositions from coal tar and simultaneously removing heavy components, particularly quinoline insoluble (QI). The results show that the low QI content (0.06 Wt%) in refined coal tar was acquired when the aromatic portion in the mixed solvent was ~30 Wt%, while the yield of refined tar increased with increasing aromatic solvent. Under the given ratio of aromatic to aliphatic (2:3 by mass), the QI contents and refined tar yields both reduced as the ratio of mixed solvent to coal tar increased. The fractions (HS, HI-TS, TI-QS) in refined tar were largely affected by the nature of solvent and solvent-tar solution. The distribution of molecular sizes in refined tars were determined by the solubility of tarry compositions in mixed solvent and the precipitating process due to the agglomeration of QI-like materials in solvent. [Received: March 3, 2018; Accepted: April 9, 2018]